Equity, Accessibility and Quality: Emerging Issues in Nigerian Education - Ogundele, Michael Olarewaju, Dados,Chales Christophe, Jankur & Nandap (PJDOL, 2023)
The paper examined the issues relating to equity, accessibility and quality education on Nigeria as an emerging issue for consideration in the modern Nigeria. However the study defined the concepts of equality, accessibility to quality educational system. Also the paper find out the causes of in equality and reasons for low accessibility to quality education in Nigeria and the associated problem from the unequal distribution of educational opportunities and methods of ameliorations was examined.